Calves as Main Reservoir of Antibiotic Resistance Genes in Dairy Farms - Salerno, Barbara; Cornaggia, Matteo; Sabatino, Raffaella; Di Cesare, Andrea; Furlan, Maddalena; Barco, Lisa; Orsini, Massimiliano; Cordioli, Benedetta; Mantovani, Claudio; Bano, Luca; Losasso, Carmen (Frontiers in Public Health, 2022)
A side effect of antibiotic usage is the emergence and dissemination of antibiotic resistance genes (ARGs) within microbial communities. The spread of ARGs among pathogens has emerged as a public health concern. While the distribution of ARGs is documented on a global level, their routes of transmission have not been clarified yet; for example, it is not clear whether and to what extent the emergence of ARGs originates in farms, following the selective pressure exerted by antibiotic usage in animal husbandry, and if they can spread into the environment. Here we address this cutting edge issue by combining data regarding antimicrobial usage and quantitative data from selected ARGs (blaTEM, blaCTXM, ermB, vanA, qnrS, tetA, sul2, and mcr-1) encoding for resistance to penicillins, macrolides-lincosamides-streptogramins, glycopeptides, quinolones, tetracyclines, sulfonamides, and colistin at the farm level. Results suggest that dairy farms could be considered a hotspot of ARGs, comprising those classified as the highest risk for human health and that a correlation existed between the usage of penicillins and blaTEM abundances, meaning that, although the antibiotic administration is not exclusive, it remains a certain cause of the ARGs' selection and spread in farms. Furthermore, this study identified the role of calves as the main source of ARGs spread in dairy farms, claiming the need for targeted actions in this productive category to decrease the load of ARGs along the production chain.